Fabrication of plate-like Ta3N5 crystals through evaporation–deposition–re-evaporation of alkali halide fluxes onto tantalum substrates. Issue 35 (6th August 2020) - Wagata, Hajime; Yanai, Minori; Kim, Daewook; Suzuki, Sayaka; Hojamberdiev, Mirabbos; Yubuta, Kunio; Terashima, Chiaki; Teshima, Katsuya
Abstract : Plate-like Ta3 N5 crystals with predominant 010 crystallographic planes covering the Ta substrate surface were fabricated through an evaporation–deposition–re-evaporation of alkali halide fluxes onto tantalum substrates. Abstract : Ta3 N5 nanostructured films have been explored as photoanodes for photoelectrochemical water splitting. Despite a number of efforts, it is still difficult to control the facet of single-crystalline Ta3 N5, which directly affects the properties, due to its harsh growth conditions. In addition, the fabrication methods of Ta3 N5 films involve complex multi-step procedures and/or require complicated equipment. In this study, we report on facile fabrication of plate-like Ta3 N5 crystals with predominant 010 crystallographic planes covering the Ta substrate surface by flux growth under an ammonia gas flow. Among alkali halide fluxes (KF, KCl, and KI), KF emerged as an effective flux for the growth of Ta3 N5 crystals. Combining KF and KI promoted further crystal growth, producing larger Ta3 N5 crystals. The crystals were confirmed as single-crystalline by TEM. The crystal growth process and shape evolution in the flux were investigated and discussed.